2016
DOI: 10.4103/0973-6131.183710
|View full text |Cite
|
Sign up to set email alerts
|

Elements of yogic practice: Perceptions of students in healthcare programs

Abstract: Background:The practice of yoga has a long history as an integrated lifestyle science. Those who have practiced yoga in its full form (including all eight traditional aspects) find that it touches almost every aspect of their inter- and intra-personal lives. Despite this rich history, the West has adopted limited aspects of yoga practice. When understood narrowly as a physical fitness practice, healthful benefits of yoga may be lost, possibly promoting body-consciousness and injury instead.Aim:To understand wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 34 publications
0
16
0
1
Order By: Relevance
“…11 In recent years, people have turned to yoga both as a method of maintaining physical health and as a way to sustain a feeling of overall well-being. 11,12,13,14 Although yoga has only been practiced in the West since its import from India around the turn of the 20th century 15 , modern yoga has become a popular practice in the US and Europe. In 2002, 10.4 million adults in the US reported having done yoga at some time 16 , while this number increased to 31 million in 2016.…”
Section: Introductionmentioning
confidence: 99%
“…11 In recent years, people have turned to yoga both as a method of maintaining physical health and as a way to sustain a feeling of overall well-being. 11,12,13,14 Although yoga has only been practiced in the West since its import from India around the turn of the 20th century 15 , modern yoga has become a popular practice in the US and Europe. In 2002, 10.4 million adults in the US reported having done yoga at some time 16 , while this number increased to 31 million in 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Second, this study did not capture the confounding variables of yoga self-efficacy 33 and yoga acceptability. 34 Third, there may have been selection bias in the sampling (i.e., convenience sampling), resulting in systematic bias that leads to skewed results. This selection bias in the sampling might have been amplified by the availability of the survey during a community event where vegan snacks were offered at the studio; class attendees who chose to attend the event (and complete the survey) may systematically differ from class attendees who did not attend the event.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] Many systematic reviews and different studies on effects on yoga for stress management in college students revealed positive effects of yoga (as a mind-body intervention) on stress reduction in college student. [ 12 13 14 ]…”
Section: Yogamentioning
confidence: 99%